The Effect of Financial Leverage on the Profitability of PT Bank Central Asia Tbk for the Period 2003-2022 - Anjang, Meifita Putri; Tumbel, Tinneke M; Rogahang, Joula J. (Productivity, 2024)
In measuring Financial Leverage and Profitability, Bank Central Asia uses the Debt to Asset ratio where Total debt is divided by Total Ase. The DAR ratio explains that the amount of debt taken by the company to fund the assets needed to run its operations and Return On Asset because it can show the company’s capacity to earn profits. The purpose of this study is to determine the effect of financial leverage on the profitability of PT Bank Central Asia Tbk from 2003 to 2022. The data analysis method used in this study is the Partial Test (T) where the results obtained show that financial leverage (DAR) has a significant negative influence on the profitability (ROA) of PT Bank Central Asia Tbk for the 2003-2022 period.